The Mediating Effect of Organizational Justice, Commitment and Motivation against the National Police Leadership on the Regional Police Personnel - Milasari, Roza; Yacob, Syahmardi; Lubis, Tona Aurora (ADPEBI International Journal of Business and Social Science, 2023)
The research aims to examine the mediating effects of organizational justice, commitment and motivation toward National Police leadership on the performance of police personnel. In this study, the questionnaires were distributed to 136 respondents, throughout the cities and districts in Jambi Province, and then the data were collected and analyzed using SEM-PLS 4.0. The research results show that improved performance police personnel is strongly influenced by the leadership style of the police, both directly and indirectly, emphasizing the importance of organizational justice, the implemented commitment and the built motivation which can mediate the relationship between the leadership and performance of the police. Therefore, police leaders must be aware of the needs of police members that through organizational justice members have confidence, which will build their commitment in performing their duties, greatly motivate the police officers. The police leadership style will drive to good performance.